2020
DOI: 10.1177/0165551520949159
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating change: Transition as a central concept for information literacy

Abstract: Transition forms a dynamic concept that has been underexplored within information literacy research and practice. This article uses the grounded theory of mitigating risk, which was produced through doctoral research into the information literacy practices of language-learners, as a lens for a more detailed examination of transition and its role within information literacy. This framing demonstrates that information literacy mediates transition through supporting preparation, connection, situatedness and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…Noting that photovoice provides a useful way to mediate the challenges of research with participants from culturally and linguistically diverse backgrounds, Lloyd and Wilkinson’s (2016, 2017) use of photovoice also draws attention to the social practices that form the foundation of learning during re-settlement. Findings from Lloyd and Wilkinson’s studies as well as from ongoing doctoral work into the information literacy practices of language-learners (Hicks, in progress) will be used as guiding studies to demonstrate these implications further.…”
Section: Visual Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noting that photovoice provides a useful way to mediate the challenges of research with participants from culturally and linguistically diverse backgrounds, Lloyd and Wilkinson’s (2016, 2017) use of photovoice also draws attention to the social practices that form the foundation of learning during re-settlement. Findings from Lloyd and Wilkinson’s studies as well as from ongoing doctoral work into the information literacy practices of language-learners (Hicks, in progress) will be used as guiding studies to demonstrate these implications further.…”
Section: Visual Research Methodsmentioning
confidence: 99%
“…The second study (Hicks, in progress) that informs this paper uses photo-elicitation methods to inform ongoing doctoral research into the information literacy practices of English-speaking undergraduate students who are learning a language abroad. Exploring how transition within a new cultural context is mediated through the enactment of information literacy practices, this study’s focus on everyday experiences meant that photo-elicitation constituted a way to explore the nuances of student meaning-making as they established themselves within a new setting.…”
Section: Guiding Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dealing with these complex life transitions has led to a recent growth of Information Science interest in the general area of life transitions, including significant work on migration (Bronstein, 2018;Lloyd, 2017;Oduntan & Ruthven, 2019), parenting (Greyson et al, 2017;Ruthven et al, 2018b), work transitions (Willson, 2019), language learners (A. Hicks, 2021), getting a new job (Jablin, 2001), and gender transition (Haimson, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…Many other disciplines are also interested in transitions and, as Hicks perceptively notes, transitions have most often been studied by disciplines that mediate change (A. Hicks, 2021). Information Science is arguably one of these disciplines and many authors have reported the value of appropriate information support during transitions.…”
Section: Introductionmentioning
confidence: 99%